2014
DOI: 10.5301/jva.5000238
|View full text |Cite
|
Sign up to set email alerts
|

Early Cannulation Prosthetic Graft (Acuseal) for Arteriovenous Access: A useful option to provide a Personal Vascular access Solution

Abstract: Early experience with the GORE Acuseal is encouraging. Patency and bacteremia rates are at least comparable to standard polytetrafluoroethylene grafts. ecAVGs have permitted cannulation within 24 hours of insertion and line avoidance in the majority of patients. Nearly three-quarters of patients achieved a definitive "personal vascular access solution" from their ecAVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 19 publications
(17 reference statements)
2
46
1
Order By: Relevance
“…In most cases they continue to be used in situations analogous to conventional AVGs, where there are no alternative autologous options. Our group has recently published information on our successful use of ecAVGs as a "bridge" to autologous AVF maturation or transplantation in selected patients (23). However, this is the first study to propose the use of ecAVG as an alternative to TCVCs for the entire dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases they continue to be used in situations analogous to conventional AVGs, where there are no alternative autologous options. Our group has recently published information on our successful use of ecAVGs as a "bridge" to autologous AVF maturation or transplantation in selected patients (23). However, this is the first study to propose the use of ecAVG as an alternative to TCVCs for the entire dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Early results with this AVG in small, single-center, early-cannulation series were encouraging with respect to patency and complication rates. 8, 9 Tozzi's experience in Europe demonstrated good patency rates and low complication rates with early cannulation of this graft. 9 The FDA clearance of the AVG was based on some of the data from the FDA-authorized clinical study reported here.…”
mentioning
confidence: 95%
“…23 This coupled with poorer outcomes from BBF in the patients over 60 years old 24 may favour a watchful waiting approach to these patients access creation. Perhaps early cannulation grafts 25,26 have a role in this subgroup of patients to permit avoidance of TCVCs but also minimize the morbidity associated with unnecessary access procedures. Such strategies would, however, need to be further evaluated given the high re-intervention rate required to maintain long-term patency of arteriovenous grafts.…”
Section: Utilization Of Avfmentioning
confidence: 99%